Views From the Street Pilot Study: Constraints and Difficulties of Using Photographs in Research of a Complex Nature Such as Homelessness. (December 2018) - Doukani, Asmae; Wei, Xingjie; Kader, Bibi; Soazandry, Fabien; Inkser, Becky
Homeless people experience a unique set of challenges leading to pervasive health and social problems. An increasing number of researchers have harnessed photographic data to gain a unique perspective of marginalised groups. The aim of the study is to explore the feasibility of using photographs in research to understand the complex environment experienced by homeless people, with a special interest in mental health. Individuals who frequently attend homeless facilities in London were sensitively approached and asked if they would be interested in taking part in the 'Views From the Street' pilot study. Once agreement was confirmed through a formal consenting procedure, participants were asked to visually capture and upload their own digital photos, along with a brief description. The collection of data highlighted a number of barriers to engagement and acceptability, including issues around the level of familiarity with the recruiter, practicalities of participation, public perception of phone use, poor technical literacy, anonymity, and disassociation with the 'homeless' label. Recommendations are made for future research utilising photographic participatory designs with the homeless population.